Perception of the local community and the role of local authority on flood problem in Sg Maong area, Kuching division, Sarawak : a case study of wee & wee Garden - Lai, Chin Moi (Universiti Malaysia Sarawak (UNIMAS), 2005)
The main objectives of the study are the assess flood problem in Wee & Wee Garden that are presently affected by flooding problem, and examine the perception of the community towards the present flood problms. Wee & Wee Garden is an oldest housing estate found along downstream of Maong Kiri River. Wee & Wee Garden was one of the most serioudly affected housing estate in the past two years flood event which happened at Maong River Catchment.